Going Beyond a Training to Foster LGBTQ Inclusive Collegiate Athletic Contexts: Next Steps - McGeorge, Christi; Walsdorf, Ashley; Toomey, Russell (Journal of Intercollegiate Sport, 2025)
This qualitative study explored how to facilitate greater inclusion of LGBTQ student-athletes and employees within the context of a collegiate athletic department that participated in a multi-level bystander intervention training for athletes, coaches, and staff. Beyond scholarship that recommends an initial educational training, there is limited literature detailing possible next steps athletic departments can take to facilitate a welcoming and inclusive environment for LGBTQ student-athletes and employees. Eighteen interviews were completed with coaches, athletic department staff, and a student-athlete. The thematic analysis revealed five themes summarizing potential next steps athletic departments could take: (1) Expand Training and Education Efforts, (2) Increase Acceptance and Accountability Across the Athletic Department, (3) Shift to Action, (4) Increase Visibility of LGBTQ Inclusion, and (5) Develop Resources for LGBTQ Students and Employees. The findings of this study provide concrete implications for creating more inclusive spaces, practices, and policies for LGBTQ individuals within collegiate athletic departments.